LncRNA NEAT1 exacerbates non-small cell lung cancer by upregulating EIF4G2 via miR-582-5p sponging - Zhang, Xin; Sun, Zhonghua; Zou, Yuepei (Archives of Biological Sciences, 2020)
Paper description: lncRNA-long non-coding RNA nuclear enriched abundant transcript 1 (NEAT1) is involved in the initiation and progression of multiple cancers. We examined the function of NEAT1 in non-small cell lung cancer (NSCLC); cytobiological and biochemical experiments were performed to study its role in an in vivo mouse model. NEAT1 potentiated the malignant potential of NSCLC cells (migration and glycolysis) through the microRNA (miR)-582-5p/eukaryotic translation initiation factor 4 gamma 2 (EIF4G2) subunit axis. The NEAT1/miR-582-5p/EIF4G2 axis could serve as a potential diagnostic or prognostic marker in NSCLC treatment. Abstract: In this study, we aimed to elucidate the role of long non-coding RNA nuclear enriched abundant transcript 1 (lncRNA NEAT1) in non-small cell lung cancer (NSCLC). Quantitative real-time polymerase chain reaction (qRT-PCR) was employed to detect the abundance of NEAT1, microRNA-582-5p (miR-582-5p) and eukaryotic translation initiation factor 4 gamma 2 (EIF4G2). Proliferation, apoptosis, metastasis and glycolytic metabolism were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) flow cytometry, transwell assays and fluorescence-based glucose and lactate assay kits. The targets of NEAT1 and miR-582-5p were predicted by the starBase website, and dual-luciferase reporter and RNA immunoprecipitation (RIP) assays were performed to verify these predictions. Western blot analysis was conducted to detect the protein expression of EIF4G2. A xenograft tumor model was built to clarify the role of NEAT1 in vivo. Results showed that NEAT1 interference inhibited proliferation, metastasis and glycolysis, and facilitated the apoptosis of NSCLC cells. MiR-582-5p was a functional target of NEAT1, and the biological influence of NEAT1 intervention on NSCLC cells was alleviated by transfection with anti-miR-582-5p. MiR-582-5p could bind to EIF4G2 messenger RNA (mRNA); it exerted its antitumor role in NSCLC cells by inhibiting EIF4G2. EIF4G2 was regulated by NEAT1/miR-582-5p signaling. NEAT1 accelerated NSCLC tumor growth via the miR-582-5p/EIF4G2 axis in vivo. In conclusion, NEAT1 affected NSCLC by elevating their malignant potential via the miR-582-5p/EIF4G2 axis. https://doi.org/10.2298/ABS200218018Z Received: February 18, 2020; Revised: April 16, 2020; Accepted: April 17, 2020; Published online: April 23, 2020 How to cite this article: Zhang X, Sun Z, Zou Y.LncRNA NEAT1 exacerbates non-small cell lung cancer by upregulating EIF4G2 via miR-582-5p sponging. Arch Biol Sci. 2020;72(2):243-52.